2014
DOI: 10.1152/ajpheart.00287.2014
|View full text |Cite
|
Sign up to set email alerts
|

Dantrolene suppresses spontaneous Ca2+release without altering excitation-contraction coupling in cardiomyocytes of aged mice

Abstract: Cardiac dysfunction in the aged heart reflects abnormalities in cardiomyocyte Ca(2+) homeostasis including altered Ca(2+) cycling through the sarcoplasmic reticulum (SR). The ryanodine receptor antagonist dantrolene exerts antiarrhythmic effects by preventing spontaneous diastolic Ca(2+) release from the SR. We tested the hypothesis that dantrolene prevents spontaneous Ca(2+) release without altering excitation-contraction coupling in aged myocardium. Left ventricular cardiomyocytes isolated from young (3 to 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 63 publications
3
15
0
Order By: Relevance
“…Cardiac dysfunction in the aged heart reflects abnormalities in myocardial ischaemia‐induced myocardial dysfunction [21]. The myocardial hypoxia‐induced oxidant strees and inflammatory responses, leading to heart injury [22].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac dysfunction in the aged heart reflects abnormalities in myocardial ischaemia‐induced myocardial dysfunction [21]. The myocardial hypoxia‐induced oxidant strees and inflammatory responses, leading to heart injury [22].…”
Section: Discussionmentioning
confidence: 99%
“…As with HFpEF patients, these conditions associate with chronic inflammation and oxidative stress. Consistent with an extramyocardial origin of HFpEF, the amplitude of cardiomyocyte Ca 2+ transients in many HFpEF-related models is normal [1518] or even enhanced [1921], suggesting an adaptive phase where Ca 2+ flux shifts toward cardiomyocyte Ca 2+ accumulation [22]. Indeed, excessive Ca 2+ entry though Ca V1.2 [19] and non-selective cation channels of the transient receptor potential (TRP) family [2325] has been observed with hypertrophic remodeling.…”
Section: Cardiomyocyte Ca2+ Handling Mechanisms In Hfpefmentioning
confidence: 95%
“…Indeed, excessive Ca 2+ entry though Ca V1.2 [19] and non-selective cation channels of the transient receptor potential (TRP) family [2325] has been observed with hypertrophic remodeling. SR Ca 2+ release through RyR 2 [15,16,21,26] and IP 3 R 2 [20] is also increased in HFpEF-related models which further enhances Ca 2+ cycling and contraction. In addition to effects on ECC, augmented Ca 2+ entry through TRPC channels [24,27,28] or release via IP 3 R 2 [29] are established upstream regulators of hypertrophic remodeling processes.…”
Section: Cardiomyocyte Ca2+ Handling Mechanisms In Hfpefmentioning
confidence: 99%
“…Previous studies have shown that spontaneous Ca 2+ release events of aged cardiomyocytes are delayed in response to dantrolene treatment however this effect is not observed in cardiomyocytes derived from young mice [ 24 ]. Since 1 μM dantrolene supplementation improved functional recovery in young hearts, we tested whether dantrolene-mediated cardiac functional recovery could be further improved after prolonged cold storage of older hearts.…”
Section: Resultsmentioning
confidence: 99%
“…It has been proposed that dantrolene can preferentially access the RyR2 binding site when the interdomain interactions are disrupted under conditions of cellular stress [ 6 ] such as with ageing. Indeed, dantrolene corrected for calcium-induced dysfunction in aged cardiomyocytes more so than in young cardiomyocytes [ 24 ] suggesting that dantrolene-mediated cardioprotection may be more prominent in hearts from older donors. In our study the cardioprotective benefit of 1 μM dantrolene-supplementation in 3-month hearts was not statistically significant for 12-month hearts.…”
Section: Discussionmentioning
confidence: 99%